Fostering autonomous learning in oral English through role play: an exploration in course setting - Li, Rui; Razali, Fazilah; Ismail, Lilliati; Muhamad, Mohd Mokhtar; Ma, Xiaolan (International Journal of Instruction, 2024)
Enhancing student motivation to manage their learning process and attain selftransformation in Oral English learning presents a notable challenge. This study emerged from a Role Play Oral English Course (RPOEC) which utilizes English cartoon film clips to enhance primary students’ oral English skills through role play, facilitating meaningful language input and output. Implemented in a Chinese context where English language exposure is limited, this qualitative case study, combined with action research, explores how autonomous learning is fostered through RPOEC. The study engaged a Grade Six class of 30 students (25 girls and 5 boys) in northern China, investigating strategies to trigger learners’ interests and form their independent learner identities autonomously, empower learners in their educational journey, encourage reflective practices in oral English learning, and involve learners in evaluative processes. Data, collected through a combination of observations, focus group discussions, and document analysis for three months, were thematically analyzed across four intertwined perspectives: situated learning, interactive communication, cooperative learning, and evaluative discussions. The paper posits that the outlined curricular approach can be tailored to educators’ needs aiming to cultivate students’ oral English skills within a situated, interactive, and collaborative learning environment, pushing learners towards autonomous engagement.